2015
DOI: 10.5966/sctm.2014-0270
|View full text |Cite
|
Sign up to set email alerts
|

Robust Expansion of Human Pluripotent Stem Cells: Integration of Bioprocess Design With Transcriptomic and Metabolomic Characterization

Abstract: Human embryonic stem cells (hESCs) have an enormous potential as a source for cell replacement therapies, tissue engineering, and in vitro toxicology applications. The lack of standardized and robust bioprocesses for hESC expansion has hindered the application of hESCs and their derivatives in clinical settings. We developed a robust and well-characterized bioprocess for hESC expansion under fully defined conditions and explored the potential of transcriptomic and metabolomic tools for a more comprehensive ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
(49 reference statements)
4
24
1
Order By: Relevance
“…Accumulation of glutamate, alanine, and to some degree glycine was observed in our bioreactor processes in line with other studies [14, 48, 49]. Although consumed in our study, asparagine, isoleucine, histidine, and threonine have been described to be secreted by hESCs in microcarrier‐based bioreactor approaches [14, 49], indicating cell line and/or process‐dependent variability in hPSCs' amino acid metabolism. In CHO cells and other fast‐proliferating cells, glycine production has been associated with high rates of serine metabolism whereas glutamate and alanine accumulation was reported to indicate distinct glutamine metabolism activity [50, 51].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accumulation of glutamate, alanine, and to some degree glycine was observed in our bioreactor processes in line with other studies [14, 48, 49]. Although consumed in our study, asparagine, isoleucine, histidine, and threonine have been described to be secreted by hESCs in microcarrier‐based bioreactor approaches [14, 49], indicating cell line and/or process‐dependent variability in hPSCs' amino acid metabolism. In CHO cells and other fast‐proliferating cells, glycine production has been associated with high rates of serine metabolism whereas glutamate and alanine accumulation was reported to indicate distinct glutamine metabolism activity [50, 51].…”
Section: Discussionsupporting
confidence: 90%
“…Applying repeated batch feeding of hESCs on matrix‐coated microcarriers in a stirred bioreactor, Silva et al recently found elevated glycolysis in 3D suspension culture compared with 2D static controls [49]. Since the same culture medium (mTeSR1) was used, the study seemingly contradicted our results.…”
Section: Discussioncontrasting
confidence: 81%
“…Bioprocess design is used in virtually every biological process, from surfactants and recombinant protein production to human stem cell culture [75][76][77].…”
Section: Bioprocess Designmentioning
confidence: 99%
“…Additionally, "omics" technologies, such as transcriptomics, metabolomics, phospho-proteomics, and epigenomics, in combination with systems biology, while allowing the identification of the molecular mechanisms (i.e., mode of actions) underlying (toxicant) effects in a high-throughput manner, are also helping to expand current knowledge of PSC profiles, which has special relevance when PSC-derivatives are intended to be used for clinical applications (Silva et al, 2015).…”
Section: Differentiationmentioning
confidence: 99%
“…One of the main advantages is its dependence on RNA and not DNA sequence (in comparison to ZFN and TALEN) as the RNA machinery base-pairing rules are simpler between an engineered RNA and the target DNA site (Sander and Joung, 2014). Meganucleases, are used for gene correction, insertion of therapeutic genes, targeted mutagenesis and virus clipping among others (Silva et al, 2015).…”
Section: Gene Editing and Gene Reporter Linesmentioning
confidence: 99%